The Development of Problem-Based Learning-Based Student Worksheets Integrated with Riau Malay Culture on Geometry Transformation Materials - Aisyah Arni Putri Simanjuntak; Zulkifli Muhammad Nuh (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to develop a Problem-Based Learning (PBL)–based Student Worksheet (LKPD) on the topic of Geometric Transformation as instructional material to facilitate ninth-grade junior high school students’ mathematical critical thinking skills. The development employed the ADDIE model, which includes the stages of needs analysis, design of content and layout, product development, implementation through small- and large-group trials, and evaluation. The research was conducted in stages involving subject-matter experts, media experts, teachers, and students. Data were collected through validation questionnaires, observations, student response questionnaires, and posttest assessments. The results indicate that the LKPD is highly valid (0.90), highly practical with percentages of 92.20% in the small-group trial and 92.32% in the large-group trial, and effective in improving learning outcomes, making it suitable for use in mathematics instruction.